Hospitality Management / An Introduction: Second Edition - Knowles Tim (Longman, 1998)
This book provides students with a solid grounding in the industry, covering all sectors of the hospitality industry, both commercial and non commercial, and sets it within the context of the tourism industry. Foreword, Preface, Acknowledgements, The Hospitality Industry: Its Links with Tourism and Travel and Leisure, Profile of the Accommodation Industry, Internationalization and Growth, Hotel Management: Dimensions and Structure, Aspects of Management, Accommodation Operations, Legislation, Restaurant and Fast Food Industry, Contract Catering Industry, Brewing Industry, Leisure Industry, Trends to the Year 2000 and Beyond, Index.